Bilateral bronchogenic cysts in a pediatric patient removed via single-sided thoracoscopy: a case report - A. Lackinger; W. Krois; A. Szelenyi; M. Metzelder (Journal of Pediatric Surgery Case Reports)
Introduction: Bronchogenic cysts are rare congenital anomalies from abnormal bronchial development. They usually present as solitary lesions; multiple cysts are extremely rare. Diagnosis and management can be challenging due to their location and symptoms. Case presentation: A 9-year-old boy presented with fever, cough, and malaise. A sputum test confirmed Mycoplasma pneumonia, and initial chest radiographs showed pneumonia and two circumscribed masses on both sides of the trachea. MRI scan suggested bilateral bronchogenic cysts: one near the right main bronchus and another more caudally on the left side, with a suspected connection between them. Two months after the resolution of the pneumonia, the patient was taken to the operating room. He was placed in left lateral prone position. We used three working ports: a 5-mm port for the camera, and two 3-mm ports for surgical instruments. We did not require single-lung ventilation during the procedure. Both cysts were excised through the right-sided thoracoscopy. The right cyst was first dissected and ligated at the base with a Roeder loop. The left cyst, found cranial to the first one and without connection to the first one, was subsequently dissected free of all attachments. Both cysts were removed from the chest into a retrieval bag. A chest tube was left in place and removed on postoperative day 3, and the patient was discharged home on postoperative day 5. Histopathology confirmed bronchogenic cysts. Conclusion: Single-sided thoracoscopy appears to be a safe and effective approach for managing selected cases of bilateral bronchogenic cysts. The left lateral prone positioning provided optimal vision, allowing access to both cysts from one side.